Hybrid assemblies of a symmetric designer protein and polyoxometalates with matching symmetry. Issue 78 (1st September 2020) - Vandebroek, Laurens; Noguchi, Hiroki; Kamata, Kenichi; Tame, Jeremy R. H.; Van Meervelt, Luc; Parac-Vogt, Tatjana N.; Voet, Arnout R. D.
Abstract : A symmetric designer protein forms hybrid complexes with different polyoxometalates and may serve as a building block for porous frameworks. Abstract : Novel bioinorganic hybrid materials based on proteins and inorganic clusters have enormous potential for the development of hybrid catalysts that synergistically combine properties of both materials. Here we report the creation of hybrid assemblies between a computationally designed symmetrical protein Pizza6-S and different polyoxometalates with matching symmetry: the tellurotungstic Anderson-Evans (Na6 [TeW6 O24 ]·22H2 O) (TEW); Keggin (H4 [SiW12 O40 ]·6H2 O) (STA); and 1 : 2 Ce III -substituted Keggin (K11 [Ce III [PW11 O39 ]2 ]·20H2 O) (Ce-K). This results in the formation of complexes with clearly defined stoichiometries in solution. Crystal structures validate the complexes as building blocks for the formation of larger assemblies.